An Overview of Approaches and Techniques used in Failure Analysis of Engineering System - Guma, T. N.; Ozoekwe, N. C. W.; Odita, K. V. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Failure of engineering system such as vehicle, building, aircraft, bridge, equipment, and industrial facility is often inevitable with calamitous consequence and/or much loss; and is highly detested. Inevitability of engineering system or component failure stems from factors such as unavoidable corrosion and wear and tear, abnormal service conditions, substandard maintenance practices, improper inspections, production errors, design errors, injudicious selection of materials, material imperfections, overloading and other service abuses of the system or component; and unknown causes. The importance and value of failure analysis in providing vital information for preventing recurrence of failure case of engineering system and the need to properly conduct the analysis has been found well documented in the literatures. Various standard approaches and techniques of engineering system failure analysis have been reviewed and presented together with 24 recent works of researchers from different backgrounds on the subject who have taken particular cases for study and evaluation. The review shows that although there are many existing failure analysis approaches and techniques of engineering systems, not all or a number of them can be suitable for every particular failure case. Critical analysis of the approaches and techniques shows that each has limitations or demerits in terms of practicability and/or cost-justification for particular failure cases. The notable issue in the review is the need to always select the best approaches and techniques for particular failure cases to assess characteristics that are present in the failed/damaged engineering system or item and those that are supposed to be present in it before failure, the differences between the damaged and undamaged system or item, and results of tests that must be performed to substantiate explanations and refine knowledge about the observed damage to correctly reveal the root cause/s of failure. Another important thing found from the review is the need to first and foremost preserve evidence of the failed system or item before using the best approaches and techniques to get as much as possible information from the field failure conditions and background realities and laboratory tests of the failed system or item. The review is posited as a readily available compendium of basic practicable information that is easy to read and understand; for consultation by concerned students, researchers, and practitioners who are not yet much experienced in failure analysis of engineering systems and need the information for furthering their knowledge on the subject.